Influence of intestinal bacteria on induction of regulatory T cells: lessons from a transfer model of colitis. Issue 11 (29th June 2005) - Strauch, U G; Obermeier, F; Grunwald, N; Gürster, S; Dunger, N; Schultz, M; Griese, D P; Mähler, M; Schölmerich, J; Rath, H C
Abstract : Background: The resident flora plays a critical role in initiation and perpetuation of intestinal inflammation, as demonstrated in experimental models of colitis where animals fail to develop disease under germ free conditions. However, the importance of exposure to commensal bacteria before the onset of colitis is unclear. Our aim was to investigate the influence of previous exposure of donor animals to bacterial antigens on colitis development using a transfer model. Methods: Clinical course and histology were evaluated after transfer of CD4 + CD62L + lymphocytes from germ free and conventionally housed donor mice into SCID recipients. Cotransfer of CD4 + CD62L + cells with CD4 + CD62L − lymphocytes from both groups of mice was initiated. Lymphocytes were analysed by FACS, polarisation potential of cells determined, and cytokines measured within the supernatant by enzyme linked immunosorbent assay. Results: Animals that received cells from germ free donors developed an earlier onset of colitis compared with mice reconstituted with lymphocytes from conventionally housed animals. Additionally, CD4 + CD62L − cells from germ free mice were not able to abrogate colitis induced by cotransfer with CD4 + CD62L + lymphocytes whereas CD4 + CD62L − T cells from normal mice ameliorated disease. The higher percentage of CD4 + GITR + expressing lymphocytes and the production of interleukin 10 after priming by dendritic cells suggests the presence of Treg cells within the CD4 + CD62L + lymphocyte subset derived from conventional housed mice and assumes a lack of Treg cells within germ free mice. Conclusion: The results indicate that bacterial antigens are crucial for the generation and/or expansion of Treg cells in a healthy individual. Therefore, bacterial colonisation is of great importance in maintaining the immunological balance.